2024
DOI: 10.1186/s12966-024-01568-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sleep pattern in relation to incident Parkinson’s disease: a cohort study

Li-Hua Chen,
Shi-Yu Sun,
Guijie Li
et al.

Abstract: Background How physical activity (PA) and different sleep traits and overall sleep pattern interact in the development of Parkinson’s disease (PD) remain unknown. Objective To prospectively investigate the joint associations of PA and sleep pattern with risk of PD. Methods Included were 339,666 PD-free participants from the UK Biobank. Baseline PA levels were grouped into low (< 600 MET-mins/week), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Participants were categorized into groups of 7–8 hours and those with <7 or >8 hours of sleep per day based on their daily sleep duration. 21 DM and hypertension were determined based on participants’ self-reporting of physician-diagnosed conditions. In the NHANES cohort, depression screening utilized the Patient Health Questionnaire-9 (PHQ9) questionnaire, with scores of ≥10 indicating depression.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were categorized into groups of 7–8 hours and those with <7 or >8 hours of sleep per day based on their daily sleep duration. 21 DM and hypertension were determined based on participants’ self-reporting of physician-diagnosed conditions. In the NHANES cohort, depression screening utilized the Patient Health Questionnaire-9 (PHQ9) questionnaire, with scores of ≥10 indicating depression.…”
Section: Methodsmentioning
confidence: 99%
“…Research indicates that both physical activity levels and ideal sleep patterns are independently associated with a lower risk of PD, whereas individuals with high physical activity levels and ideal sleep patterns have the lowest risk of developing PD. Therefore, enhancing physical activity levels and sleep quality may be promising targets for intervention to prevent PD (72). A study noted that treadmill training increased cortical striatal neuroplasticity and dopamine release, thereby improving sleep quality (73).…”
Section: Improving the Quality Of Life And Sleep Disorders For Parkin...mentioning
confidence: 99%
“…Firstly, while sleep disturbances seem to be closely related to PD in observational studies 2 , 3 , there is no convincing evidence of any causal relationship of self-reported and objective sleep traits with the risk of PD in Mendelian randomization analysis 4 , 5 . However, genetic variants in Mendelian randomization analysis may not be an accurate substitute for sleep because genes can only account for a relatively small proportion of sleep phenotypic variation, and thus, the non-significant relationship may be attributed to insufficient statistical power.…”
mentioning
confidence: 99%